Il dialogo tra diritto ecclesiastico e diritto costituzionale (Stato, Chiese e pluralismo confessionale, 2023)
Fifty years after the conference in which Law and Religion Scholars held a dialogue with Constitutional Scholars in Siena, central issues of that discussion are recalled, and those of a future debate are envisaged, with the hope that both disciplines might benefit from it